Synthesis of a novel fused pyrrolodiazepine-based library with anti-cancer activity. Issue 15 (11th April 2018) - Malik, Neha; Iyamu, Iredia D.; Scheidt, Karl A.; Schiltz, Gary E.
Graphical abstract: Highlights: A library combining features of diazepines and pyrrolidinediones was prepared. Highly efficient Mannich-type intramolecular cyclization is described. Library explore new chemical space with highly 3D and Sp 3 -rich molecules. Several compounds have significant anti-cancer activity. Abstract: Development of drugs for new and persistent diseases will increasingly rely on the expansion of accessible chemical space to allow exploration of novel molecular targets. Here we report the synthesis of a library of novel fused heterobicyclic small molecules based on the 1, 4-diazepine and 2, 4-pyrrolidinedione scaffolds. Key chemical transformations included a Mannich-type condensation and chemoselective N -acylation reactions. Screening shows anti-cancer activity of several library compounds which suggests translational potential of this novel chemical scaffold.